Pengelompokkan Jenis Minyak Mentah Menggunakan Metode X-Means Clustering - IRFANI - ZUHRUFILLAH (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2021)
The price of crude oil in Indonesia is still very volatile it cause of strongly influenced by the demand and supply mechanism. The other factor is the fundamental factor, the non-fundamental factor, and the influence and policy of OPEC factor. Refined petroleum is indispensable in life, used for various human purposes for fuels such as gasoline and kerosene, asphalt, and some of the chemical reagents used to make plastics and medicines. These crude oil prices Information in Indonesia are open and officially published by the Ministry of Energy and Mineral Resources website from 2017 until now. That information is about the monthly prices of several major oil refineries in Indonesia. There is no information about the resume of price fluctuations in one oil refinery, and there is no information on the grouping of oil refineries based on the selling price of the refinery. This study aims to group crude oil price categories in Indonesia using the x-means method. This study is one of the efforts to provide general information about crudes oil price clusters based on major refineries in Indonesia to the public. The results showed that the grouping types of crude oil prices throughout 2020 with the X-Means method contained four optimal clusters with the highest price characteristic being the type of crude oil which is cluster 1, then cluster 0, cluster 3, and the last is cluster 2.